Chinese Medicines Improve Perimenopausal Symptoms Induced by Surgery, Chemoradiotherapy, or Endocrine Treatment for Breast Cancer - Wang, Shuo; Lin, Hongsheng; Cong, Weihong (Frontiers in Pharmacology, 2019)
The application of surgery, chemoradiotherapy and endocrine treatment successfully increase survival rates of breast cancer patients. However, perimenopausal symptoms, the main side effects of these treatments, often afflict patients and reduce their quality of life. Perimenopausal symptoms include vasomotor symptoms, sleep problems, arthromuscular symptoms and osteoporosis. Currently, there is no satisfactory treatments for perimenopausal symptoms that result from these treatments. Therefore, alternative and complementary therapies including herbal medicines represented by Chinese medicines (CMs), acupuncture, massage and psychotherapy are increasingly being expected and explored. In this paper, we review the effects and potentials of several CM formulae, along with some active ingredients or fractions from CMs, Chinese herbal extracts and other herbal medicines, which have drawn attention for improving perimenopausal symptoms in breast cancer patients. We also elaborate their possible mechanisms. Moreover, further studies for evaluation of standardized clinical efficacy should be scientifically well-designed and continuously performed to investigate the efficacy and mechanisms of CMs for perimenopausal symptoms due to breast cancer therapy. The safety and value of estrogen-containing CMs for breast cancer should also be clarified.